2009
DOI: 10.1371/journal.pone.0004149
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Intentions and Outcomes among Women on Antiretroviral Therapy in Rural Uganda: A Prospective Cohort Study

Abstract: BackgroundAntiretroviral therapy (ART) may influence the biological, social and behavioral determinants of pregnancy in HIV-infected women. However, there are limited longitudinal data on the reproductive intentions and outcomes among women on ART in Africa.Methodology /Principal FindingsUsing a prospective cohort design, we analyzed trends in desire for children and predictors of pregnancy among a cohort of 733 HIV-infected women in rural Uganda who initiated ART between May 2003 and May 2004 and were followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
167
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(196 citation statements)
references
References 36 publications
25
167
4
Order By: Relevance
“…Despite the risk of mother to child transmission of HIV, significant proportion of parents living with HIV continued to desire to have children [5][6][7][8]. Studies also revealed that HIV-positive women encountered unintended pregnancies with associated risk of mother to child transmission of HIV [9][10][11]. The experience of repeated untended pregnancy among HIV positive women particularly adolescents is partially due to inconsistence use of contraceptives [12].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the risk of mother to child transmission of HIV, significant proportion of parents living with HIV continued to desire to have children [5][6][7][8]. Studies also revealed that HIV-positive women encountered unintended pregnancies with associated risk of mother to child transmission of HIV [9][10][11]. The experience of repeated untended pregnancy among HIV positive women particularly adolescents is partially due to inconsistence use of contraceptives [12].…”
Section: Introductionmentioning
confidence: 99%
“…[17,18,3] In particular, a multi-country analysis of Demographic and Health Survey (DHS) data from nine countries revealed lower contraceptive uptake among HIV-positive women with prior knowledge of their status than counterparts who were HIV-negative in three of the countries included in the study: Zimbabwe, Kenya, and Malawi. [16] The apparent disconnect between fertility desire and contraceptive uptake among HIV-positive women has been attributed to diverse factors ranging from social desirability or stigma surrounding childbearing for HIV-positive individuals [19] to low contraceptive use among HIV-positive women based on the perception that they and their partners were infertile due to HIV infection [20]. Despite the general association between HIV-positive status and low fertility intention, perceived risk or uncertainly about HIV status have both been linked to desires to accelerate childbearing.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 While rates of consistent condom use among couples who are aware of their status are higher, unprotected sex among these couples is still common 27,28 and has been shown to be associated with desire for pregnancy 29 and alcohol use. 30 PLHIV who inconsistently use condoms and who simultaneously have higher viral loads due to non-adherence to antiretroviral treatment (ART) or because they are not yet eligible for ART are at high risk for transmitting HIV to negative sex partners.…”
Section: Introductionmentioning
confidence: 99%